Contributions and benefits reflected in the translation of beginner translators through the proper use of translation tools (Cat Tools) - Solano de Callejas, Nubia Carolina (Universidad de El Salvador. Facultad de Ciencias y Humanidades., 2024)
We found out that this specialization in Translation helps translators to apply different ways to produce a new text translation using tools like Cat Tools. This contributes especially for beginner translators’ translation; the purpose of this investigation is mostly to reduce time’s handing costumer translations in order to maximize your experience. for example when we translate a birth certificate in the past with no internet connection this time to traduce this document can be handing to the client in 3 or 4 nowadays using cat Tools is the fast way to get Satisfactory results of translated texts and image editing of a document can be attained through the study of accurate translation techniques and the practice of Cat tools This report presents how the six-month course of Specialization in Translation Fundamentals was developed; through this course, students were able to understand and practice the fundamentals of translation techniques and the usage of Cat Tools for translation. As conclusion, we realized that using those tools, students learned how to translate documents such as diplomas, birth certificates, and records, to provide the translation of the source language to the target language. This report encompasses the translation works completed throughout the semester using translation techniques and Computer-Assisted Translation tools. Cat Tools play a significant role in modern translations as they facilitate time management while translating, image editing, or group translating.